ON THE REACHABILITY PROBLEM OF A VISCOELASTIC BEAM DURING A SLEWING MANEUVER - Leugering, Günter (International Series of Numerical Mathematics, 1989)
Congrès International conference on control of distributed parameter systems. 4 (1988) 1989, vol. 91, pp. 249-261 (12 ref.)